(untitled) (Nexo Revista Científica, 2023)
Aim of present study is to pursuit with the abundant of resources provided by the firms to make customer satisfied and corresponding consequences which are in the favor of customers. Nevertheless, present study results indicated that customer satisfaction not necessarily in the outcome that are persuaded. In addition, study focused more on customer delight which explored innovative consequences and antecedents that are in the interest of the service firms. Study then proposed the conceptual framework and considered the links of employee expertise, employee effort to customer surprise which in turn leads to customer delight and percent of budget spent, shopping frequency is considered as moderating between customer surprise and customer delight. Data collection process were conducted in a grocery store. Study hypotheses and relationships were tested using SPSS (V.22). Findings of study shows all the considered variables are positively linked with each other.